1985
DOI: 10.1111/j.1348-0421.1985.tb00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Cell Envelopes of Rickettsia tsutsugamushi

Abstract: Isolation and purification of the envelope of a microorganism are important for analysis of the host-parasite relationship and its immunological properties. In fact, such studies are in progress on various microbes.Rickettsia tsutsugamushi, a causative agent of scrub typhus, seemed to have a unique envelope among the members of genus Rickettsia. Differences between these rickettsial envelopes were recognized by morphological observations (5). Purification procedures for the other rickettsiae by Renografin dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(6 reference statements)
0
3
1
Order By: Relevance
“…A previous comparative DNA analysis of genes from six strains revealed that the Tsa has four regions of amino acid variability interspersed among five regions of amino acid conservation (25). Previous studies have shown that a type-specific B-cell determinant for the Karp strain is present in the VD I region (aa 105 to 133) (41); however, in this study, strainspecific MAb KI4 bound to the VD II region (aa 151 to 174), which partially overlaps with AD II. Moreover, we obtained similar results with group-specific MAb KI57.…”
Section: Discussioncontrasting
confidence: 77%
“…A previous comparative DNA analysis of genes from six strains revealed that the Tsa has four regions of amino acid variability interspersed among five regions of amino acid conservation (25). Previous studies have shown that a type-specific B-cell determinant for the Karp strain is present in the VD I region (aa 105 to 133) (41); however, in this study, strainspecific MAb KI4 bound to the VD II region (aa 151 to 174), which partially overlaps with AD II. Moreover, we obtained similar results with group-specific MAb KI57.…”
Section: Discussioncontrasting
confidence: 77%
“…Interestingly, the predicted T-cell epitopes are primarily located outside of the variable domains of TSA56 ( Supplementary Figure S2 ). 32 By contrast, antigenic determinants for antibody responses generally overlap with variable domains of TSA56, 42 , 43 and immunological pressure on the major outer membrane protein during vertebrate host infection might be a crucial driver of genetic diversification of O. tsutsugamushi . 1 Discovery of the preservation of T-cell epitopes in the major outer membrane protein among different genotypes represents a significant advancement toward generating universal and protective T-cell responses that encompass the diverse genotype strains of O. tsutsugamushi .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the individual serum showed a great variety in the reactivity. Additionally, from the 1251 labeling experiments of intact rickettsiae and the analysis of components of the purified envelope of the rickettsiae, 54-56K, 35K, and 21-25K polypeptides were demonstrated to be constitutional proteins of the rickettsial SERA OF SCRUB TYPHUS surface, while the 60K polypeptide was estimated to be the rickettsial inner protein (7,10). It is not known, at present, why an individual patients would show such a variety in the immune response and why the 60K polypeptide is antigenic only in a few cases of human infections.…”
Section: Discussionmentioning
confidence: 99%